2019
DOI: 10.1039/c9sc01682a
|View full text |Cite
|
Sign up to set email alerts
|

Systematic exploration of the mechanical properties of 13 621 inorganic compounds

Abstract: Exploring elastic properties of 13 621 crystals highlights how rare auxeticity and negative linear compressibility are.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 58 publications
(76 reference statements)
4
39
0
Order By: Relevance
“…The zero-temperature elastic and mechanical properties of several 2D-based materials, including their het-erostructures and the less studied trichalcogenides, have been computed (see Table 1 in the Supplementary Material). 11 The predicted elastic and mechanical properties are in excellent agreement with existing data in literature 5,8,[12][13][14][15] . For example, our predicted Y 2D ∼135.86 N/m is in good agreement with recent experiments, which span from 129 to 185 N/m 14,[16][17][18] and previous first-principles calculations that reported values 122 -146 N/m.…”
Section: Introductionsupporting
confidence: 79%
See 1 more Smart Citation
“…The zero-temperature elastic and mechanical properties of several 2D-based materials, including their het-erostructures and the less studied trichalcogenides, have been computed (see Table 1 in the Supplementary Material). 11 The predicted elastic and mechanical properties are in excellent agreement with existing data in literature 5,8,[12][13][14][15] . For example, our predicted Y 2D ∼135.86 N/m is in good agreement with recent experiments, which span from 129 to 185 N/m 14,[16][17][18] and previous first-principles calculations that reported values 122 -146 N/m.…”
Section: Introductionsupporting
confidence: 79%
“…5,6 Moreover, the accurate knowledge of the full elastic tensor enables the determination of many other important elastic, mechanical, and thermodynamic properties of materials that are essential for screening, design, and discovery of new materials. 7,8 Recently, and specifically for 2D-based materials (Fig. 1), high-throughput elastic properties of several materials have been calculated and collected in some materials' databases such as the Materials Project, the JARVIS-DFT, and the Computational 2D Materials Database.…”
Section: Introductionmentioning
confidence: 99%
“…It is common for databases to contain over 10% of erroneous data. Indeed, one study found that 14% of the data describing the elastic properties of crystals in the Materials Project is unphysical 15 . Cleaning steps include removing duplicates, entries with missing values, incoherent or unphysical values, or data type conversions.…”
Section: Data Cleaning and Curationmentioning
confidence: 99%
“…10 In the area of negative linear compressibility (NLC), relatively few works have discussed its possible occurrence in zeolitic materials. 24 However, a recent systematic study of inorganic materials has shown that it is more frequent than usually estimated, 25 and it is not as rare as a property as negative Poisson's ratio, or auxeticity. 26 Auxeticity was known to occur in some zeolites since the seminal works of Grima 27 and Evans.…”
Section: Introductionmentioning
confidence: 99%